2021
DOI: 10.1101/2021.08.30.456472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A gap-free tomato genome built from complementary PacBio and Nanopore long DNA sequences reveals extensive linkage drag during breeding

Abstract: The assembly and scaffolding of plant crop genomes facilitates the characterization of genetically diverse cultivated and wild germplasm. The cultivated tomato has been improved through the introgression of genetic material from related wild species, including resistance to pandemic strains of Tobacco Mosaic virus (TMV) from Solanum peruvianum. Here we applied PacBio HiFi and ONT nanopore sequencing to develop independent, highly contiguous and complementary assemblies of an inbred TMV-resistant tomato variety… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Cutting-edge sequencing and bioinformatic improvements (Baid et al, 2021; Silvestre-Ryan & Holmes, 2021), like the ONT Guppy5 basecaller, will likely assist more efficient assembly, resulting in higher QV and reduced computational load; however, currently the ONT specific requirements might be computationally prohibitive, especially when assembling many samples. Currently there are no approaches to co-assembling HiFi and ONT data that fully exploit the different advantages of the reads; however, HiFi and ONT assemblies can be merged post hoc (Alonge et al, 2021) which may improve contiguity (van Rengs et al, 2021), although we observed only minor increases (Supplementary Table 8).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Cutting-edge sequencing and bioinformatic improvements (Baid et al, 2021; Silvestre-Ryan & Holmes, 2021), like the ONT Guppy5 basecaller, will likely assist more efficient assembly, resulting in higher QV and reduced computational load; however, currently the ONT specific requirements might be computationally prohibitive, especially when assembling many samples. Currently there are no approaches to co-assembling HiFi and ONT data that fully exploit the different advantages of the reads; however, HiFi and ONT assemblies can be merged post hoc (Alonge et al, 2021) which may improve contiguity (van Rengs et al, 2021), although we observed only minor increases (Supplementary Table 8).…”
Section: Discussionmentioning
confidence: 90%
“…These results indicate that optimal minigraph pangenomes would use high-quality, complete genomes as the backbone, like emerging T2T assemblies (Belser et al, 2021;Nurk et al, 2021;Rengs et al, 2021). Alternatively, reference-free approaches to pangenomes (Armstrong et al, 2020) may also circumvent these issues.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, when going beyond model plants and major established crops, challenges remain. Whilst resolving homozygous genomes ( van Rengs et al., 2021 ) and pangenomes ( Bayer et al., 2020 ) of crops with a medium genome size is now achievable with the advent of novel sequencing technologies ( Mascher et al., 2021 ), challenges remain with consistent gene annotation and ontology developments. Rapid progress is being made with more mature tools, facilitating structural ( Holst et al, 2023 ) and functional genome annotation ( Bolger et al., 2018 ; Schwacke et al., 2019 ), whilst plant genome data continues to be gathered in comprehensive databases ( Vandepoele, 2017 ).…”
Section: Novel Technologies and Approaches For Crop Improvementmentioning
confidence: 99%